Makkiyah Dan Madaniyah : Pengertian, Karakteristik Dan Pembagiannya Dalam Al-Qur’an - Fiimaratus Sholihah; Hakmi Hidayat; Naila Nur Fitria; Moh Fikri Tamami; Muhammad Akbar (CV. ITTC INDONESIA, 2024)
The concepts of Makkiyah and Madaniyah are two important terms in historical studies Islam refers to two different periods of the revelation of the Holy Qur’an, namely the period Makkah and Medina period. The Makkiyah period refers to the verses of the Holy Qur’an revealed during the prophetic period in Mecca before the Hijrah, during the period Madaniyah refers to verses revealed after the Hijrah, the time of the Prophet Muhammad moved to Medina. These two periods not only differ geographically,but also have different social, political and legal contexts that influence it development of Islamic teachings. The Makkiyah period was marked by fundamental messages about monotheism, justicesocial, and moral courage. Verses in this period often emphasize its importance faith, fortitude and patience in facing challenges. Meanwhile, period Madaniyah is characterized by more detailed legal arrangements, the formation of society Muslims first, and upholding social justice through established laws. A deep understanding of Makkiyah and Madaniyah concepts helps us to see the evolution of Islam from a broader historical perspective. Differences in the messages and context of these two periods provide a better understanding of how Islamic teachings develop and adapt to challenges and socio-political changes at that time. By understanding the differences between the two this period, we can appreciate the complexity and depth of Islamic teachings as wellits relevance in the contemporary context.